Game therapy a new approach to treat women facing mixed urinary incontinence: A study protocol. Issue 5 (3rd April 2020) - Oliveira, Maria Clara Eugênia; Bezerra, Livia Oliveira; Melo Ângelo, Priscylla Hellouyse; de Oliveira, Maiara Costa; Silva‐Filho, Edson; Ribeiro, Tatiana Souza; Pegado, Rodrigo; Micussi, Maria Thereza Albuquerque Barbosa Cabral
Abstract: Aims: To describe a pelvic floor muscle training (PFMT) isolated and associated with game therapy (PFMT + GT) for women facing mixed urinary incontinence (MUI) during climacteric period. Methods: To standardize a randomized controlled clinical trial intervention, a protocol was created, in an attempt to decrease women's symptomatology generated by MUI, through pelvic floor and abdomino‐loin‐pelvic muscles strength, and endurance. This study protocol will be composed of 32 volunteers, divided into two groups of 16. They will perform PFMT isolated or PFMT + GT, twice a week during 8 weeks. Interventions will last 40 minutes and will be divided into warming (5 minutes), training (30 minutes), and 5 minutes will be composed of resting time between exercises (1 minute each). Isolated PFMT sessions will be performed through four modalities of exercises: diaphragmatic, bridge, abdominal (plank), and pelvic mobility. PFMT + GT training will be carried out by using Wii Fit Plus games, such as Lotus Focus, Penguin Slide, Basic Step, and Hula Hoop from Wii equipment. Assessments will occur before, after, and 1 month after interventions. Vaginal manometry, 1‐hour Pad Test, International Consultation on Incontinence Questionnaire—Short Form (ICIQ‐SF), and Patient Global Intervention (PGI) will be used to evaluate the sample. Conclusions: It is expected greater increase on pelvic floor muscle (PFM) strength, endurance, vaginal pressure for PFMT + GG. Moreover, it is supposed that PFMT + GT volunteers present better treatment adherence due to games motivational inclusion.